Carbon Sequestration and Storage by Gainesville's Urban Forest - Francisco Escobedo; Jennifer A. Seitz; Wayne Zipperer (EDIS)
FOR-210, a 3-page illustrated fact sheet by Francisco Escobedo, Jennifer A. Seitz, and Wayne Zipperer, presents analysis of data to determine the extent to which Gainesville’s urban and natural trees mitigate the effects of climate change by sequestering CO2. Includes references. Published by the UF School of Forest Resources and Conservation, March 2009.